Cancel culture and its underlying motivations in Singapore - Tan, Beverly Hui Ru (Nanyang Technological University, 2021)
This study seeks to explore Singaporeans’ understanding of cancel culture and their motivations behind participating in it. Using a mixed-methods approach, this study builds on a series of in-depth interviews with 20 participants who have participated in cancel culture with regards to the recent saga involving local influencer, Xiaxue, and a national survey involving 800 respondents. As a result of the interviews, the study defines cancel culture as the public shaming on a social media platform, carried out or supported by a group of people, which aims to hold people accountable for socially incorrect or unacceptable behaviour. Using the framework of the Theory of Planned Behaviour, this study found attitude, subjective norms, perceived behavioural control, outcome expectancy, and general Belief in a Just World as significant predictors of cancelling behaviour through intention. This study contextualises cancel culture in the local context while providing insight on its predictors and the effects of individual morals on such behaviour.